Reliability and validity of a questionnaire to evaluate diabetic patients' intention to adopt health information technology: a pilot study - Ahmad, Barroon Isma'eel; Ahlan, Abdul Rahman (JATIT & LLS, 2015)
All the efforts put in developing questionnaire by a researcher are in vain if it measures what is not intended to measure. A questionnaire can only be useful if it produces meaningful and trustworthy data. The aim of this study was to develop and assess the validity and reliability of an instrument to measure the perception and attitude of diabetic patients toward acceptance of Health Information Technology (HIT). An extended Technology Acceptance Model (TAM) based questionnaire was distributed to a sample of 80 diabetic patients. The content validity was assessed by experts, while Exploratory Factor Analysis (EFA) was used to measure the construct validity. Cronbach's alpha was used to measure the internal consistency of the questionnaire. The response rate of the questionnaire was 93%. In the exploratory factor analysis, seven factors that correspond with the constructs were extracted using principal component analysis. The factors examined using varimax rotations explained 72.15%, 74.21%, 72.67%, 80.84%, 72.72%, 74.22% and 74.84% variance in the respective constructs. Construct validity was measured using convergent and discriminant validity. Most of the variables load in the range of 0.60 - 0.98, which shows a good convergent validity, and the significant loading of the variables on one factor without cross-loadings is an evidence of the discriminant validity. Similarly, the average Cronbach's alpha coefficient of the seven extracted components was 0.822 indicating a good internal consistency or reliability. This study presents the result of reliability and validity of the extended TAM based instrument for assessing the perception and attitude of diabetic patients toward acceptance of HIT. The findings of this study showed the feasibility of using the questionnaire, since it has high reliability and validity.